2013
DOI: 10.3357/asem.3342.2013
|View full text |Cite
|
Sign up to set email alerts
|

Motion Sickness Prevention by an 8-Hz Stroboscopic Environment During Air Transport

Abstract: These results support the use of stroboscopic illumination as a nonpharmacologic countermeasure for motion sickness related to retinal slip. However, due to the uncontrolled nature of the flights, the possibility that these results could have been influenced by differences in motion between flights cannot be excluded. This technology should be investigated in other forms of transportation (i.e., ground vehicles).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Transcutaneous electrical nerve stimulation of the posterior neck and the right Zusanli acupoint was found to be effective in reducing simulator sickness symptoms and alleviating cognitive impairment . Recently, stroboscopic illumination at 8 herts, by ambient strobe light or by liquid crystal display shutter glasses, reduced the severity of MS symptoms and improved the performance on the vigilance task in soldiers exposed to a nauseogenic flight in a helicopter .…”
Section: Nonpharmacological Countermeasuresmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation of the posterior neck and the right Zusanli acupoint was found to be effective in reducing simulator sickness symptoms and alleviating cognitive impairment . Recently, stroboscopic illumination at 8 herts, by ambient strobe light or by liquid crystal display shutter glasses, reduced the severity of MS symptoms and improved the performance on the vigilance task in soldiers exposed to a nauseogenic flight in a helicopter .…”
Section: Nonpharmacological Countermeasuresmentioning
confidence: 99%
“…peripheral accuracy), and provides an opportunity to examine eye-hand coordination (EHC) in relation to performance evaluation due to a paucity of research in this area. Research using stroboscopic exposure has been conducted into the prevention of air travel sickness [21], space motion sickness [22], and has been shown to be an effective countermeasure in these particular ecologically valid environmental settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation also echoes an early investigation showing that predictive visual cues produced by displaying moving point prior to visual stimulus enhanced self-motion perception and relieved MS in immersive virtual environment (Fujita, 2004 ). Webb et al have reported that 8 Hz stroboscope illumination in cabin significantly reduced the incidence of nausea in helicopter passengers compared with non-stroboscope condition (Webb et al, 2013 ). The authors also claimed that the nausea scores were less under the 8 Hz setting than the 4 Hz setting which appears to reduce distorted vision-induced MS via transiently improving gaze stability (reduce retinal slip) during locomotion (Jones and Mandl, 1981 ; Bos and Bles, 2004 ; Han et al, 2005 ; Reschke et al, 2006 ; Webb et al, 2013 ; Muntaseer Mahfuz et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Webb et al have reported that 8 Hz stroboscope illumination in cabin significantly reduced the incidence of nausea in helicopter passengers compared with non-stroboscope condition (Webb et al, 2013 ). The authors also claimed that the nausea scores were less under the 8 Hz setting than the 4 Hz setting which appears to reduce distorted vision-induced MS via transiently improving gaze stability (reduce retinal slip) during locomotion (Jones and Mandl, 1981 ; Bos and Bles, 2004 ; Han et al, 2005 ; Reschke et al, 2006 ; Webb et al, 2013 ; Muntaseer Mahfuz et al, 2018 ). However, as the nature of flight was not controlled, whether or not the vibration of helicopter matched the stroboscopic intensity remained unknown.…”
Section: Discussionmentioning
confidence: 99%